PEMBUATAN LKS BERBASIS ICT DENGAN MENGINTEGRASIKAN MSTBK MATERI GERAK DAN SIFAT ELASTIK DALAM MENCAPAI KOMPETENSI SISWA KELAS XI SMA - Atika Ulya Akmal (Universitas Negeri Padang, 2014)
Integrating Science, ICT, and character values in learning are important in education. The reality in schools this integration is not optimal done. Solution of this problem is applying of worksheet based ICT by integrating MSTBK in the learning of Physics. The purpose of this research is to generate worksheet for learning Physics that have good description, validity, practicality, and effectiveness. Type of this research is Research and Development (R & D). This research uses before and after design in limited testing. There are three data analysis techniques, those are validity, practicality, and effectiveness analysis. Based on product and data analysis, there are two results of this research. First, the validity of student worksheet based ICT is high with average value 80.4 and 96.39. This student worksheet consist of main menus, those are introduction, worksheets, evaluation, download, and additional menu in the form of chatting and discussion forum. Second, student worksheet based on ICT is practice and effective used in physics learning process.